2017
DOI: 10.1111/cas.13311
|View full text |Cite
|
Sign up to set email alerts
|

High expression of CPNE3 predicts adverse prognosis in acute myeloid leukemia

Abstract: CPNE3, a member of a Ca2+‐dependent phospholipid‐binding protein family, was identified as a ligand of ERBB2 and has a more general role in carcinogenesis. Here, we identified the prognostic significance of CPNE3 expression in acute myeloid leukemia (AML) patients based on two datasets. In the first microarray dataset (n = 272), compared to low CPNE3 expression (CPNE3 low), high CPNE3 expression (CPNE3 high) was associated with adverse overall survival (OS, P < 0.001) and event‐free survival (EFS, P < 0.001). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Lin et al found the metastasis-promoting roles of copine-III in non-small cell lung cancer (NSCLC) via a quantitative proteomic analysis 26. Recently, Fu et al reported that high expression of CPNE3 predicts adverse prognosis in AML 27. Our results showed that copine-III would participate in sorafenib-resistance in advanced HCC treatment.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Lin et al found the metastasis-promoting roles of copine-III in non-small cell lung cancer (NSCLC) via a quantitative proteomic analysis 26. Recently, Fu et al reported that high expression of CPNE3 predicts adverse prognosis in AML 27. Our results showed that copine-III would participate in sorafenib-resistance in advanced HCC treatment.…”
Section: Discussionsupporting
confidence: 54%
“… 26 Recently, Fu et al reported that high expression of CPNE3 predicts adverse prognosis in AML. 27 Our results showed that copine-III would participate in sorafenib-resistance in advanced HCC treatment. These data expand our understanding of copine-III in human cancers.…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, CPNE3 plays a pivotal role in other diseases. High expression of CPNE3 predicted an adverse prognosis in acute myeloid leukemia 12 , and it was identified as a novel candidate gene for schizophrenia 13 . However, in NSCLC, the underlying mechanism of CPNE3 remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Overlap of differentially regulated phosphorylation sites from the current PRE-R vs. PRE-NR study with those identified in previously published MS-based phosphoproteomics studies; Table S1: Proteomic differences between AML patients when comparing AML cells derived from responders vs. non-responders to antileukemic treatment based on ATRA and VP; Table S2: Regulated proteins that have both phosphorylation and expression fold change (FC) in the PRE-R vs. PRE-NR study; Table S3: Pair-wised fold change (FC) of regulated protein expression in responder patients considering quantitative values at pre-treatment (PRE), day 3 (3D) and day 8 (8D) of the ATRA–VP–TP treatment; Table S4: Pair-wised fold change (FC) of regulated protein expression in non-responder patients considering quantitative values at pre-treatment (PRE), day 3 (3D) and day 8 (8D) of the ATRA–VP–TP treatment; Table S5: Pair-wised fold change (FC) of differentially regulated phosphorylation sites in responder patients considering quantitative values at pre-treatment (PRE), day 3 (3D) and day 8 (8D) of the ATRA–VP–TP treatment; Table S6: Pair-wised fold change of differentially regulated phosphorylation sites in non-responder patients considering quantitative values at pre-treatment (PRE), day 3 (3D) and day 8 (8D) of the ATRA–VP–TP treatment. References [ 26 , 48 , 49 , 53 , 71 , 90 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 …”
mentioning
confidence: 99%